A Clinical and Economic Evaluation of ORIF Management for Calcaneal Fractures with and without Adjunctive Umbilical Cord. Issue 4 (November 2022) - Stewart, Chris
Category: Hindfoot Introduction/Purpose: The number of calcaneus fractures per year continues to increase in the United States, resulting in an increased number of open reduction and internal fixation (ORIF)procedures to repair these injuries. These surgeries are notorious for post-operative complications, including post-surgical wound healing problems that occur in 16 to 43% of patients. Umbilical cord (UC) allograft has anti-inflammatory and anti-scarring properties and has been shown to promote healing of cutaneous wounds. The objective of this study was to evaluate the clinical and economic outcomes related to wound complications after ORIF management of calcaneal fractures with and without adjunctive UC. Methods: A clinical and economic evaluation was performed based on information pertaining to ORIF management obtained from the published literature and our previous clinical data of ORIF for calcaneal fractures with (n=20) and without adjunctive UC (n=20). Results: After ORIF for calcaneal fractures, 10% of patients that received adjunctive UC required wound care compared to 35% of patients didn't receive the adjunctive treatment. Similarly, the readmission and reoperation rate were higher in the control group compared to the UC treatment group (30% vs 10%, respectively). Available cost-effectiveness data demonstrated that treatment with UC results in an average cost-savings of $2, 775.50 per person over a five-year period (total cost of $330, 500 vs. $386, 010 in the UC and control group, respectively). Using available data that includes costs incurred from time off work, adjunctive UC allograft treatment resulted in an average cost-savings of $14, 377.50 per patient over a four-year period (total cost of $704, 260 vs. $991, 810 in the UC and control group, respectively). Conclusion: Wound complications remain a significant burden to patient recovery and an economic burden to payors and providers. Based on our observed complications rates, adjunctive use of UC during ORIF management of calcaneal fractures may not only decrease wound complications but also reduce socioeconomic costs.